Affect, inflammation, and health in urban at-risk civilians. (September 2018) - Lin, Cliff; Michopoulos, Vasiliki; Powers, Abigail; Wingo, Aliza P.; Schwartz, Ann; Bradley, Bekh; Ressler, Kerry J.; Gillespie, Charles F.
Abstract: Positive and negative affect are both associated with health outcomes. Using validated measures, we examined associations between affect, self-reported measures of health, and objective measures of systemic inflammation in a cross-sectional sample of outpatient subjects recruited from an urban county hospital. Participants (n = 1055) recruited from the Grady Trauma Project in Atlanta, GA underwent standardized interviews including self-report measures of psychiatric symptoms and physical health. A subset (n = 246) consented to an assay of serum C-reactive protein (CRP). Regression models including positive affect as the predictor variable with covariates of age, gender, income, trauma load, depression and PTSD symptoms, were significantly associated with physical health domain scales of the Short Form-36 Health Survey (SF-36) of general health (R 2  = 0.212; p < 0.001) and physical functioning (R 2  = 0.154; p = 0.013). No association was observed using negative affect as the predictor variable. While greater serum CRP concentrations were associated with less positive affect (r = −0.137; p = 0.038), this relationship did not remain significant (p = 0.250) when controlling for demographic variables, body mass index, trauma load, and psychiatric symptoms. Future studies using larger samples or samples with more variance for CRP and positive and negative affect may be helpful in investigating the relationship between CRP and positive and negative affect. Our results support the hypothesis that positive affect contributes beneficially to physical health. Development of strategies to enhance positive affect in at-risk populations may be a meaningful way to improve their health.